Amorphous Silica Controls Water Storage Capacity and Phosphorus Mobility in Soils - Schaller, Jörg; Frei, Sven; Rohn, Lisa; Gilfedder, Benjamin Silas (Frontiers in Environmental Science, 2020)
Two problems currently facing agriculture are drought and the availability of mineable phosphorus minerals used for fertilization. More frequent and longer drought periods are predicted to threaten agricultural yields in the future. The capacity of soils to hold water is a highly important factor controlling drought stress of plants during the growing phase. High phosphorus availability in soils is also necessary for high agricultural yields, however over application has also led to a range of environmental problems, foremost being the eutrophication of waterways. Amorphous silica (ASi) has been suggested as one solution to mitigate both water and phosphorus availability. In this work we analyzed the effect of ASi on phosphorus mobility and the soil water storage of a sandy soil. In a lysimeter experiment we found that ASi strongly increased the water storage capacity of soils (up to 180 % by addition of 3 wt. % ASi). Furthermore, the ASi is in direct competition with phosphorus for sorption sites on iron oxides and other soil minerals increasing nutrient mobilization and increasing potential bioavailability for plants. Following calibration to the lysimeter experiment a process based hydrological model was used to extrapolate experimental results to a sandy agricultural soil with and without ASi for one year. For the soil with ASi, the water storage capacities for the yearly scenario were up to 40 kg/m² higher compared to the untreated soil. Our results suggest that ASi enhances the water storage capacity and phosphorus mobility in soil and that this may be one way to mitigate the predicted climate change related drought stress in sandy soils.